The change in capacity and service delivery at public and private hospitals in Turkey: A closer look at regional differences - Ergin Işıl; Aksan Hediye AD; Ocek Zeliha (BMC, 2010)
Abstract Background Substantial regional health inequalities have been shown to exist in Turkey for major health indicators. Turkish data on hospitals deserves a closer examination with a special emphasis on the regional differences in the context of the rapid privatization of the secondary or tertiary level health services. This study aims to evaluate the change in capacity and service delivery at public and private hospitals in Turkey between 2001-2006 and to determine the regional differences. Methods Data for this retrospective study was provided from Statistical Almanacs of Inpatient Services (2001-2006). Hospitals in each of the 81 provinces were grouped into two categories: public and private. Provinces were grouped into six regions according to a development index composed by the State Planning Organisation. The number of facilities, hospital beds, outpatient admissions, inpatient admissions (per 100 000), number of deliveries and surgical operations (per 10 000) were calculated for public and private hospitals in each province and region. Regional comparisons were based on calculation of ratios for Region 1(R1) to Region 6(R6). Results Public facilities had a fundamental role in service delivery. However, private sector grew rapidly in Turkey between 2001-2006 in capacity and service delivery. In public sector, there were 2.3 fold increase in the number of beds in R1 to R6 in 2001. This ratio was 69.9 fold for private sector. The substantial regional inequalities in public and private sector decreased for the private sector enormously while a little decrease was observed for the public sector. In 2001 in R1, big surgical operations were performed six times more than R6 at the public sector whereas the difference was 117.7 fold for the same operations in the same regions for the private sector. These ratios decreased to 3.6 for the public sector and 13.9 for the private sector in 2006. Conclusions The private health sector has grown enormously between 2001-2006 in Turkey including the less developed regions of the country. Given the fact that majority of people living in these underdeveloped regions are uninsured, the expansion of the private sector may not contribute in reducing the inequalities in access to health care. In fact, it may widen the existing gap for access to health between high and low income earners in these underdeveloped regions.